Rural minimum living standard guarantee (rural Dibao) program boosts children's education outcomes in rural China. Issue 1 (8th January 2021) - He, Zixuan; Fang, Xiangming; Rose, Nathan; Zheng, Xiaodong; Rozelle, Scott
Abstract : Purpose: To combat poverty in China's rural areas, Chinese government has established an unconditional cash transfer program known as the Rural Minimum Living Standard Guarantee (Rural Dibao) Program. Interestingly, despite the importance of education in breaking cycles of poverty, little is known about Rural Dibao's impact on rural children's education. This study investigates Rural Dibao's impact on rural children's learning outcomes by first examining targeting issues within the program, exploring a causal relationship between Rural Dibao and learning outcomes, and then exploring potential mechanisms and heterogeneous effects. Design/methodology/approach: Fixed effects model and propensity score weighting method and data from China Family Panel Studies (CFPS) from the years 2010 and 2014 were used. Findings: The results suggest that the Rural Dibao program suffers from high levels of targeting error, yet is still effective (i.e., program transfers generally still go to people in need). The fixed effects and propensity score weighting models find that program participation raises rural children's standardized test scores in CFPS Chinese-language and math tests. In investigating mechanisms, increased education expenditure seems to connect Rural Dibao participation to increased learning results. The heterogeneity analysis shows that poorer, non-eastern, not left behind, younger or male children benefit from the program (while others have no effect). Originality/value: These findings suggest that Rural Dibao participation boosts rural children's learning, which could indicate a long-term anti-poverty effect, and that if the program can resolve targeting problems, this effect could be even greater.